Implementation of the Haversine Algorithm in the Development of a WebGis - Agung Pambudi; Ahmad Fikri Hanif; Syauqi Rahmat (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
Monitoring transmission tower disruptions require a system capable of presenting location information accurately and quickly to support the decision-making process. Limitations in the presentation of spatial data and the manual process of identifying disruption locations pose obstacles to improving the effectiveness of network infrastructure management. This study aims to develop a web-based transmission tower disruption monitoring system that integrates geospatial visualization and distance calculations to determine the nearest tower. The system is built using web technology with digital map support to display tower locations and disruption points interactively. Backend testing results using k6 show that all endpoints have a 100% success rate without failure, with response times ranging from 1.73 ms to 4430 ms, with the majority being below 1000 ms. All response values are still within the tolerance limit (<5000 ms), indicating stable system performance in handling various types of requests. In addition, the results of User Acceptance Testing (UAT) show that all system modules run according to user requirements.